Evaluating the feasibility and acceptability of an adapted fencing intervention in breast cancer surgery post-operative care: the RIPOSTE pilot randomized trial - Hasnaoui, Sabrine; Van Hoye, Aurélie; Soudant, Marc; Rotonda, Christine; Carvalho de Freitas, Andréia; Peiffert, Didier; Delattre, Cécile; Raft, Julien; Temperelli, Margaux; Allado, Edem; Hily, Oriane; Chenuel, Bruno; et al. (Frontiers in Oncology, 2024)
Background: Adapted physical activity programs have shown promising results in reducing the physical, social and psychological side effects associated with breast cancer, but the extent to which they can be effectively adopted, implemented and maintained is unclear. The aim of this study is to use the framework to guide the planning and evaluation of programs according to the 5 following keys: Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework to evaluate a fencing program under the French acronym RIPOSTE (Reconstruction, Image de soi, Posture, Oncologie, Santé, Thérapie, Escrime) literally in English (Reconstruction, Self-Image, Posture, Oncology, Health, Therapy, Fencing). This program is an innovative intervention focused on improving the quality of life (QoL) of breast cancer surgery patients through fencing.A convergent mixed methods pilot study was conducted to preliminary evaluate the different RE-AIM dimension of the pilot program. Twenty-four participants who have just undergone surgery for invasive breast cancer were randomly allocated in two groups : one group started immediately after their inclusion (Early RIPOSTE group) and the other started 3 months following their inclusion (Delayed RIPOSTE group). Participants answered a questionnaire at inclusion and at the end of the program on QoL, shoulder functional capacity, fatigue, anxietydepression and physical activity.Results: RIPOSTE program was able to reach mainly young and dynamic participants, attracted by the originality of fencing and keen to improve their physical condition. Regarding effectiveness, our results suggest a trend to the improvement of QoL, shoulder functional capacity, fatigue and anxiety-depression state, even without any significant differences between the Early RIPOSTE group and the Delayed RIPOSTE group. The cooperation, exchanges and cohesion within the group greatly facilitated the adoption of the program, whereas interruptions during school vacations were the main barriers. The intervention was moderately well implemented and adherence to the protocol was suitable.RIPOSTE is an acceptable and effective program for involving breast cancer survivors in physical activity, that needs to be tested at a larger scale to investigate its effectiveness, but has the potential to be transferred and scaled up worldwide.